Synthesizing guidelines for facilitating elderly-smartphone interaction - Cunha, Bruna C. R.; Rodrigues, Kamila R. H.; Pimentel, Maria da Graça C. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2019)
Nowadays, using mobile and communication technologies helps the elderly population to stay active by promoting social interactions and independence in many daily tasks, such as paying their bills. Therefore, we can identify many efforts for the digital inclusion of the elderly. However, just offering access to the new technologies, such as touch-based smartphones and tablets, is not enough to ensure effective digital inclusion. Developers need to design apps that consider the inherent losses of the aging process, in order to create more accessible computational solutions. As developers of apps for the elderly population, we struggle to provide a good User Experience for these users. We carried out a literature review to identify guidelines for the design of inclusive interfaces, however, literature guidelines are divergent in some cases, especially in aspects related to touch interaction. To clarify some of these differences, we conducted a case study with elderly to analyze their touch interaction with mobile devices. Twelve seniors interacted with a mobile digital game developed to evaluate touch-based interactions. We recorded and analyzed their in-game touch performance data. Preliminary observations indicated the difficulties of these elders in the interaction characterized by drag and drop and pinch gestures. As result, a list of guidelines resulting from the literature and the study is proposed.